STRATEGI PENGEMBANGAN BISNIS BIBIT TANAMAN HUTAN (KASUS PT SARBI MOERHANI LESTARI, BOGOR) - Joko Purwono; Sri Sugyaningsih; Reny Novianti (Neo-Bis, 2008)
The research was aimed to identification and analyze internal and external condition that influence the business development in PT Sarbi Moerhani Lestari and to formulate the correct strategic in order to develop the business. The research was conducted in PT Sarbi Moerhani Lestari for 2 months since April until June 2007. The method used was case study by purposive sampling by collected primary and secondary data. The data was analyze by IFE matrix, EFE matrix, IE matrix, SWOT, and AHP (Analitical Hierarchy Process).    The result from identification of internal factor showed that the main strenght is administration completeness with score is 0,368 . And the main weakness is dependence of government market with score is 0,088. Meanwhile, from identification of external factor showed that the main oportunity is the future auction system with technical and cost spesification, and the main threat is auction system with the lowest cost assesment..Competitive position of company from the result of IE matrix showed that  the position in V cell. It  means  that company have average internal condition and the company’s  response of external condition is middle.     From all alternative strategic, the first priority is  increasing time and cost efficiency based on company environment change to over come the competition and low price of forest plant seed  with priority score  is 0,378.